Public-Private Partnership Enhances Water Utility's Performance in Armenia - Tokhmakhian, Zaruhi; Eiweida, Ahmed (World Bank, Washington, DC, 2012)
Public-Private Participation (PPP) schemes were successfully implemented in several water utilities in Armenia, yielding excellent results for the development of the water and wastewater sectors. Armenia is one of the few countries in the region to have had such a successful PPP experience. For many years after the collapse of the Soviet economy, most of the water supply and sanitation systems in Armenia were in disrepair. The country was faced with increasing demand, deteriorating assets and dilapidated infrastructure, which resulted in a steadily decreasing and costly provision of services. Despite an abundance of water in the country, for almost all Armenians, water was available for only a few hours a day. In recent years, Armenia has made significant strides in reforming the water sector by developing policies, enacting laws, and drawing up plans, programs and strategies aimed at improving water service provision.